The Fracture Resistance of Additively Manufactured Monolithic Zirconia vs. Bi-Layered Alumina Toughened Zirconia Crowns When Cemented to Zirconia Abutments. Evaluating the Potential of 3D Printing of Ceramic Crowns: An In Vitro Study - Amirali Zandinejad; Marta Revilla-León; Mohammad Mujtaba Methani; Leila Nasiry Khanlar; Dean Morton (Dentistry Journal, 2021)
(1) Background: This study compared the fracture resistance of additively manufactured monolithic zirconia and bi-layered alumina toughened zirconia crowns on implants. (2) Methods: Maxillary model with a dental implant replacing right second bicuspid was obtained. Custom abutments and full-contour crowns for additively manufactured monolithic zirconia and bi-layered alumina reinforced zirconia crowns (n = 10) were fabricated. The crowns were cemented to implant-supported zirconia abutments and the assembly fixed onto resin blocks. Fracture resistance was measured using a universal testing machine at a crosshead speed of 2 mm/min. A Kruskal–Wallis test was used to analyze the data. (3) Results: Although additively manufactured monolithic zirconia crowns demonstrated a higher mean fracture resistance than bi-layered alumina toughened zirconia crowns, statistical analysis revealed no significant difference in fracture resistance between the two groups. All specimens fractured at the implant–abutment interface. (4) Conclusions: Additively manufactured bi-layered alumina toughened zirconia crowns demonstrated similar fracture resistance to additively manufactured monolithic zirconia crowns when cemented to implant-supported zirconia abutments.